Faim2 contributes to neuroprotection by erythropoietin in transient brain ischemia. Issue 3 (20th February 2018) - Komnig, Daniel; Gertz, Karen; Habib, Pardes; Nolte, Kay W.; Meyer, Tareq; Brockmann, Marc A.; Endres, Matthias; Rathkolb, Birgit; Hrabě de Angelis, Martin; Schulz, Jörg B.; Falkenburger, Björn H.; et al.
Abstract: Delayed cell death in the penumbra region of acute ischemic stroke occurs through apoptotic mechanisms, making it amenable to therapeutic interventions. Fas/CD95 mediates apoptotic cell death in response to external stimuli. In mature neurons, Fas/CD95 signaling is modulated by Fas‐apoptotic inhibitory molecule 2 (Faim2), which reduces cell death in animal models of stroke, meningitis, and Parkinson disease. Erythropoietin (EPO) has been studied as a therapeutic strategy in ischemic stroke. Erythropoietin stimulates the phosphatidylinositol‐3 kinase/Akt (PI3K/Akt) pathway, which regulates Faim2 expression. Therefore, up‐regulation of Faim2 may contribute to neuroprotection by EPO. Male Faim2‐deficient mice (Faim2 −/− ) and wild‐type littermates (WT) were subjected to 30 min of middle cerebral artery occlusion (MCAo) followed by 72 h of reperfusion. EPO was applied before (30 min) and after (24 and 48 h) MCAo. In WT mice application of EPO at a low dose (5000 U/kg) significantly reduced stroke volume, whereas treatment with high dose (90 000 U/kg) did not. In Faim2 −/− animals administration of low‐dose EPO did not result in a significant reduction in stroke volume. Faim2 expression as measured by quantitative reverse transcription polymerase chain reaction (qRT‐PCR) increased after low‐dose EPO but not with high dose. An extensive phenotyping including analysis of cerebral vessel architecture did not reveal confounding differences between the genotypes. In human post‐mortem brain Faim2 displayed a differential expression in areas of penumbral ischemia. Faim2 up‐regulation may contribute to the neuroprotective effects of low‐dose erythropoietin in transient brain ischemia. The dose‐dependency may explain mixed effects of erythropoietin observed in clinical stroke trials. Abstract : Delayed cell death in the penumbra region of acute ischemic stroke occurs through apoptotic mechanisms, making it amenable to therapeutic interventions. The signaling pathway by which erythropoietin (EPO) protects neurons in cerebral ischemia has not been resolved. We hypothesize that Fas‐apoptotic inhibitory molecule 2 (Faim2) is involved in EPO‐mediated neuroprotection, in a pathway that also involves blockade of the death receptor Fas, also known as apoptosis antigen 1. We tested our hypothesis in an animal model of transient cerebral ischemia. Results from this study revealed that EPO reduces ischemia‐related cell death in mice but failed in clinical stroke studies. Fas/CD95 signaling contributes to ischemia‐related cell death and can be inhibited by Faim2. Mice lacking Faim2 were not protected by EPO doses that reduced ischemia‐related cell death in wild type mice. We found up‐regulated Faim2 after EPO and suggest that Faim2 may contribute to EPO‐mediated neuroprotection after stroke. FADD, Fas‐associated death domain‐containing protein.